When Biology Isn’t Destiny: Implications for the Sexuality of Women Without Children - Daniluk, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2007)
Despite recent changes in the role options available to many women, a strong link between sexuality, maternity, and womanhood continues to be reinforced within most cultures throughout the world. Irrespective of women's other life accomplishments and creative labours, motherhood is still considered by many to be the hallmark of mature womanhood_a symbol of women's ultimate destiny and fulfillment. The implications of this maternal imperative for the sexual self-esteem and agency of heterosexual women without children are explored in this paper. Four recommendations are made for working with the increasing number of women who, for reasons of choice or circumstances, do not become mothers.